Stress and fracture analysis of short flat bars with projections using boundary element method (BEM) - Lim, Hao Liang (Nanyang Technological University, 2024)
Short flat bars with projections are widely used as load bearing components to transmit load in the axial direction and they can be commonly found in many applications today. However, projection on these components causes an abrupt change in cross sectional area, which could increase stress concentration around the area subjected to geometric discontinuities. Even though fillets can be introduced to the component to reduce the stress concentration around the geometric discontinuity, but improper design, material and manufacturing defects could propagate cracks around the fillet region and eventually lead to failure. Hence, various studies have been conducted to understand the effects of geometry on stress concentration factor (SCF) and stress intensity factor (SIF) at these high stress regions. The geometry parameters, boundary conditions such as local and remote restraints, loading conditions such as axial and shear loading were varied in this project. This project utilizes Boundary Element Method (BEM) for the computation of SCF for components without crack and the overall SIF for components with crack. The first part of this project focused on short flat bars with projections without crack and the SCF obtained at high stress regions were compared against different geometric parameters, loading conditions and boundary restraints. For the second part of the project, a crack was introduced at the node where the component experiences the highest stress and the overall SIF obtained were compared against different geometric parameters and crack lengths. Through the investigation of the results obtained from BEM, it can be concluded that by increasing R/d ratio was effective in the reduction of SCF for components without crack. On the other hand, by increasing R/d ratio for components with crack led to minimal effects on reduction of overall SIF. It was observed that increasing D/d ratios had a greater effect in the reduction of overall SIF for components with crack. The effects of varying other geometric parameters were discussed in depth in this report.